Risk Factors Associated with Falls in Hospitalized Older Adults Patients - Miaohong Chen MPH; Yajuan Tao BS; Zhexin Lin MPH; Shiliang Li MPharm; Wen He PhD; Ling Zhang MD (Gerontology and Geriatric Medicine)
Background: Given the complexity of existing assessment methods and the scarcity of specialized geriatric healthcare professionals in China, this study aimed to investigate the risk factors for falls in hospitalized older adults patients. Methods: From July 2018 to July 2020, 112 older adults patients hospitalized in the Department of Geriatrics of our hospital were enrolled and grouped into the low-( n  = 12), medium-( n  = 58), and high-( n  = 42) (fall) risk groups according to the Johns Hopkins Fall Risk Assessment. The patient’s clinical characteristics, smoking, alcohol consumption, disease, falling history, osteoporosis medication, mobility, Barthel index, MMSE, and JHFRAT score were compared between groups. Results: The high-risk group had the oldest age, and the lowest weight, BMI, as well as highest rate of stroke history and sarcopenia among the three groups. Multivariate linear regression analysis revealed that stroke history ( B  = 2.66, 95% CI = [0.43, 4.89]; p  = .020) and gait speed ( B  = −4.78, 95% CI = [−8.74, −0.76]; p  = .020) were the significant factors associated with fall risk in hospitalized older adults patients. Conclusions: The results suggested that hospitalized older adults patients with stroke history and low gait speed had higher fall risk. These findings may be helpful for fall prevention in hospitalized older adults patients.